Legend tripping: a contemporary legend casebook - McNeill, Lynne S., editor; Tucker, Elizabeth, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Explores the practice of legend tripping, where individuals or groups travel to a site where an urban legend is thought to have taken place. Legend tripping is depicted throughout vernacular (contemporary and historical) culture and an expression of humanity's interest in the frontier between life and death.--Provided by publisher.
Introduction / Lynne S. McNeill and Elizabeth Tucker -- Early studies / Elizabeth Tucker -- Legend-tripping in Ohio / Bill Ellis -- Adolescent legend trips as teenage cultural response / Patricia M. Meley -- Legend-trips and satanism / Bill Ellis -- Playing with fear / S. Elizabeth Bird -- Shame old roads can't talk / Tim Prizer -- Ostensive healing / Carl Lindahl -- Contemporary ghost hunting and the relationship between proof and experience / Lynne S. McNeill -- "There's an app for that" / Elizabeth Tucker -- Living legends / Lynne S. McNeill.
Keywords: Urban folklore -- United States; Legends -- United States; Culture and tourism -- United States; Haunted places -- United States; Supernatural